Flexural Strength Deterioration of Steel Fiber Reinforced Concrete Due to High Temperature - Kadir, Mohammed R. A.; Musa, Ismail H. (Sulaimani Journal for Pure and Applied Sciences, 1997)
There are important cases in which concrete is exposed to high temperatures such as fire, chimneys and refractory structures, etc. exposing concrete to high temperature causes strength deterioration, increase in drying shrinkages, and the reduction in bond strength with reinforcement. This investigation is carried out to study the effect of steel fiber addition on flexural strength deterioration of concrete exposed to high temperatures in the range of 20o to 800o C. The following variables are taken in to account: type of mix, fiber content and aspect ratio, heating duration and type of cooling. Test results have shown that the inclusion of steel fibers in concrete reduces the amount of strength loss due to heating, the degree of strength deterioration depends on the fiber content and high temperatures, and the bulk flexural strength lose occurs within two hours of heat exposure.